(untitled) (Applied Biological Research, 2024)
Curcuma haritha (Zingiberaceae) is a less explored endemic ethnomedicinal herb of north Kerala (India). The aim of present study was to evaluate the anti inflammatory potential and phytochemical profile of methanolic rhizome extract of C. haritha. The preliminary assays performed were, the proteinase inhibition and the protein denaturation inhibition tests, followed by cyclooxygenase, lipoxygenase, iNOS and cellular nitrite activity/expression assays in LPS stimulated RAW 264.7 cells. The toxicity of the extract was studied using MTT assay and the expression of COX-2 inflammatory protein in treated cells was determined by indirect ELISA. The phytochemical profiling was done by GC-MS analysis. All the assays revealed a dose-dependent anti-inflammatory effect in vitro. The inhibition of inflammatory enzymes, COX-2, Lox and iNOS were observed as 62.16 ± 0.49, 57.25 ± 1.98 and 56.74 ± 2.73%, respectively, at maximum concentration (100 µg mL-1). The cellular nitrite levels and expression of COX-2 mediator protein also decreased in treated cells proving the anti inflammatory effect of the extract. GC-MS screening revealed the presence of 54 phytoconstituents including anti-inflammatory compounds like curcumenol, chamazulene, etc., Therefore, in the light of above results, C. haritha can be considered as a potential anti-inflammatory drug source plant.